FINANCIAL PERFORMANCE, INSTITUTIONAL OWNERSHIP, SIZE, AND FIRM VALUE : A STRUCTURAL EQUATION MODELING APPROACH - N Rusnaeni; Hari Gursinda; Hendro Sasongko; Dani Rahman Hakim (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study analyzed the effect of financial performance, institutional ownership, and firm size on firm value. This study used the partial least square structural equation modeling (PLS-SEM) analysis to examine which indicators best measure financial performance. This study employed panel data from Indonesia's 13 property and real estate sector companies. This study found that the return on assets ratio is the only indicator measuring financial performance. This study also found that financial performance positively affects firm value. On the other hand, institutional ownership affected the firm value negatively. In contrast, this study failed to prove any positive effect of firm size on firm value. This study indicated that investors tend to pay close attention to profitability as the primary consideration when investing in property and real estate companies' shares. Another implication of this research is that the significant institutional ownership in a company tends to make investors uninterested